The effect of exercise on serum immunoglobulins and interleukins in secondary school children - Singh, Harbindar Jeet; Mat, Ishak (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2018)
Epiderniologica1 evidence has shown that regular exercise increases the inunune function while strenuous exercise leads to im1nune suppression (Pedersen & Toft, 2000). Accumulating facts have shown that regular exercise offers SOJne protection against malignancy at an early stage of life (Pedersen & Toft, 2000). In this regard, cytokine released into the circ~lalion have been irnplicated as a causative mediator of exercise-induced itnrnune perturbation. Suzuki and his colleagues (2000) did a study on tnarathon runners and reported a significant increase in the concentration of JL-2 • \Vhile a significant decrease in JL-6, -8 and -10. Cytokines play a multifunctional role in the irnnnme systern. They mediate conununication between and \vithin iantnune and nonitnnume cells. They play a major role in initiating the in1n1une responses. I Ience, alteration or perturbation in cytokine regulation 1nay produce ton rnnrk~rl impacf on fhc irnmm1E' syst<:-Jn. Thi~ m!ly 1c-:-td ~e an increase in susceptibility to infection by rnicroorganis1ns that will irnpair the individual's life. The beneficial effects of exercise are very well accepted. Exercise needs to be started fro1n an ear1y age of life and throughout ones life span. Consequently, the habit of doing exercise needs to be promoted earlier especiaiJy throughout school life. The in1pact of exercise on adolescents and its beneficial effects on health has been a focus of recent research (Murray, J 994). Regular exercise is presumed to play a 1najor role in preventing several leading degenerative diseases of modern societies. The United States Departn1ent of Health and Hun1an Service (1992) noted that childhood is a critical tirne for developing healthy attitudes and behaviour patterns in relation to tobacco use, diet, physical activity and other health-related behaviours that ... may persist into adulthood (Fiectcher et a/., 1996 ). The proper an1ount of exercise is presmnably important for the optin1al development and health status of children. Too 111uch or too little exercise n1ay have so1ne adverse erlects (McKeag, 1991 ) . • In a recent survey, of tnore than 13 000 teenagers, only a third said they were moderately to vigorously active five or more times per week (Gordon-Larsen et a/., 1 999). A study by Sallis & McKenzie in 1991 of 759 children who took achievement test after three different physical interventions, found that students in a health-related physical education (PE) progran1 did as well academically as students who spent half as rnuch title each W-Veek in PE. Consequently, there is a need to focus on the impact of exercise on the imtnune systern in adolescents. There is a paucity of data about this particular issue in Malaysia. l-Ienee, the present study is designed to detennine the effect of moderate exercise on the imrnune·systetn of adolescents with special reference to cytokines.